GALACTOSE-INDUCED SKIN AGING: THE ROLE OF OXIDATIVE STRESS - Umbayev, Bauyrzhan; Askarova, Sholpan; Almabayeva, Aigul; Saliev, Timur; Masoud, Abdul-Razak; Bulanin, Denis (Hindawi, 2020)
Skin aging has been associated with a higher dietary intake of carbohydrates, particularly glucose and galactose. In fact, the carbohydrates are capable of damaging the skin’s vital components through nonenzymatic glycation, the covalent attachment of sugar to a protein, and subsequent production of advanced glycation end products (AGEs). This review is focused on the role of D-galactose in the development of skin aging and its relation to oxidative stress. The interest in this problem was dictated by recent findings that used in vitro and in vivo models. The review highlights the recent advances in the underlying molecular mechanisms of D-galactose-mediated cell senescence and cytotoxicity. We have also proposed the possible impact of galactosemia on skin aging and its clinical relevance. The understanding of molecular mechanisms of skin aging mediated by D-galactose can help dermatologists optimize methods for prevention and treatment of skin senescence and aging-related skin diseases.
Keywords: advanced glycation end products; AGEs; aging; skin aging; Research Subject Categories::MEDICINE; Type of access: Open Access; oxidative stress